Characterization of antipsychotic medications, amino acid signatures, and platelet-activating factor in first-episode psychosis - Bracha Erlanger Avigdor (Elsevier, 2021)
First-episode psychosis refers to individuals early in the course of psychotic illness. Identifying the underlying biological processes, including biomarkers, is essential for improving diagnosis and treatment. We performed metabolomics profiling of plasma from a group of first-episode psychosis patients and matched neurotypical controls. Using global metabolomics profiling, we identified antipsychotic or antidepressant medication in 22 individuals diagnosed with first-episode psychosis, closely matching the drug prescription history. There were significant differences in levels of amino acids or their derivatives, including decreases in DL-arginine, L-histidine, DL-serine and threonine as well as increases in L-glutamic acid, ornithine, and proline. Using targeted metabolomics profiling of 408 compounds in plasma samples we identified significant differences in six compounds including decreases in serotonin and arginine as well as increased levels of sarcosine, proline, cis-4-hydroxyproline and trans-4-hydroxyproline. Platelet-activating factor levels were significantly elevated in the FEP cohort. These findings suggest potential biomarkers that require validation in independent cohorts, and in several cases provide supporting evidence for previously reported observations.